If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.1x + -4 = 2.1x Reorder the terms: -4 + 3.1x = 2.1x Solving -4 + 3.1x = 2.1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.1x' to each side of the equation. -4 + 3.1x + -2.1x = 2.1x + -2.1x Combine like terms: 3.1x + -2.1x = 1x -4 + 1x = 2.1x + -2.1x Combine like terms: 2.1x + -2.1x = 0.0 -4 + 1x = 0.0 Add '4' to each side of the equation. -4 + 4 + 1x = 0.0 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 0.0 + 4 1x = 0.0 + 4 Combine like terms: 0.0 + 4 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s | | -5y+1(2)=5 | | -(2-8x)=3(8x-1)-16x+1 | | t(n)=-8-7(447) | | -3x-2(5y-7)=-12 | | -5+3x=3(x-6)+13 | | 180(n-2)=156 | | t(n)=14-3(447) | | 6w=8w-40 | | 1.04x/3.14=7.98 | | 19u-17u-u=20 | | 3x^3-x*y=5 | | x+6=x-4 | | ln8/ln4 | | ln8/lnr4 | | ln8/lv4 | | 9m+10-4m=-5 | | (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 | | p(x)=5x^2-3x+2 |